The effectiveness of web based flipped classroom model toward the skill college students in writing poem - Saniman, Saniman; Pratiwi, Cerianing Putri; Widyaningrum, Heny Kusuma; Putri, Widyarini Susilo (Universitas Ahmad Dahlan, 2025)
This study aims to determine the effectiveness of the web-based flipped classroom model in students' poetry writing skills. The method used is quantitative experiments. The participants were categorized or randomly placed in two groups, namely the experimental class and the control class. In this study, the researcher used a 3rd semester student population of 149 students. The samples taken were classes 3B and 3C with each class totaling 32 students. The research sample was taken using cluster random sampling. The research data was in the form of student poetry writing results collected using the test method, while the hypothesis test used the t-test. The result of this study is that the t-value 7.586 > t-table is 2,040, so based on decision-making through the comparison of the t-value with the t-table, it can be concluded that Ho is rejected and H1 is accepted. It can be concluded that the web-based flipped classroom learning model is effective for learning to write poetry. It is recommended to conduct long-term research in order to form independent learning habits and deep understanding of students on an ongoing basis.